A rationale for combination ampicillin and daptomycin in renal transplant patients with enterococcal infective endocarditis. (2018) - Castro-Lainez, Miriams Teresita; Sierra-Hoffman, Miguel; Valladares, Victoria; Tillman, Tywaun; Iznaloa-Esquivel, Oscar A.; Howell, Alan; Fader, Robert; Winn, Richard; Jinadatha, Chetan
Abstract: Treatment of enterococcal endocarditis in patients with history of renal transplantation is complicated. Treatment failure and/or drug toxicities are not uncommon. Treatment with ampicillin and daptomycin in a renal transplant patient has been rarely reported. Here we report a patient who was successfully treated with this novel combination.